The Effects of Chlormadinone Acetate on Lower Urinary Tract Symptoms and Erectile Functions of Patients with Benign Prostatic Hyperplasia: A Prospective Multicenter Clinical Study - Kiyohide Fujimoto; Yoshihiko Hirao; Yasuo Ohashi; Yasuhiro Shibata; Kohzo Fuji; Hidenori Tsuji; Katsuhito Miyazawa; Mikinobu Ohtani; Ryoji Furuya; Eitetsu Boku (Advances in Urology)
Purpose. To evaluate the effects of chlormadinone acetate (CMA), progesterone-derived antiandrogen, on lower urinary tract symptoms (LUTS) and erectile functions of benign prostatic hyperplasia (BPH). Methods. A multicenter, single-cohort prospective study was conducted. A total of 114 patients received CMA for 16 weeks. The endpoints were changes in International Prostate Symptom Scores (IPSS), IPSS-QOL, International Index of Erectile Function-5, Qmax prostate volume, and residual urine volume. Results. Significant improvements were observed in IPSS from week 8 to week 48 (32 weeks after treatment). IPSS-QOL improvements were also significant from week 8 to week 48. Qmax increased to a maximum at Week 16 and remained elevated throughout the study. Moreover, a decrease of 25% in prostate volume was observed at Week 16. IPSS, QOL, and Qmax changes during the study were not different between the previously treated and untreated patients. IPSS storage subscore changes differed between the age groups. Few severe adverse reactions were observed, except for erectile dysfunction. Conclusions. CMA rapidly and significantly reduced prostate volume and improved voiding and storage symptoms and QOL. Our results suggest that CMA is safe and beneficial, especially for elderly patients with LUTS associated with BPH.